Multidrug-resistant organism-peritoneal dialysis associated peritonitis: clinical and microbiological features and risk factors of treatment failure - Guo, Shizheng; Yang, Liming; Zhu, Xueyan; Zhang, Xiaoxuan; Meng, Lingfei; Li, Xinyang; Cheng, Siyu; Zhuang, Xiaohua; Liu, Shengmao; Cui, Wenpeng (Frontiers in Medicine, 2023)
Background Multidrug-resistant (MDR) bacterial infection causes difficulty in the therapy of peritoneal dialysis-associated peritonitis (PDAP); however, there are few studies on multidrug-resistant organism (MDRO)-PDAP. In view of growing concerns about MDRO-PDAP, the aim of this study was to investigate the clinical features, risk factors of treatment failure, and causative pathogens of MDRO-PDAP. Methods In total, 318 patients who underwent PD between 2013 and 2019 were included in this multicenter retrospective study. Clinical features, patient outcomes, factors related to treatment failure, and microbiological profiles associated with MDRO-PDAP were analyzed and risk factors for treatment failure associated with Escherichia coli (E. coli) were further discussed. Results Of 1,155 peritonitis episodes, 146 eligible episodes of MDRO-PDAP, which occurred in 87 patients, were screened. There was no significant difference in the composition ratio of MDRO-PDAP between 2013–2016 and 2017–2019 (P > 0.05). E. coli was the most prevalent MDRO-PDAP isolate, with high sensitivity to meropenem (96.0%) and piperacillin/tazobactam (89.1%). Staphylococcus aureus was the second most common isolate and was susceptible to vancomycin (100%) and linezolid (100%). Compared to non-multidrug-resistant organism-PDAP, MDRO-PDAP was associated with a lower cure rate (66.4% vs. 85.5%), higher relapse rate (16.4% vs. 8.0%), and higher treatment failure rate (17.1% vs.6.5%). Dialysis age [odds ratio (OR): 1.034, 95% confidence interval (CI): 1.016–1.052, P < 0.001] and > 2 previous peritonitis episodes (OR: 3.400, 95% CI: 1.014–11.400, P = 0.047) were independently associated with treatment failure. Furthermore, longer dialysis age (OR: 1.033, 95% CI: 1.003–1.064, P = 0.031) and lower blood albumin level (OR: 0.834, 95% CI: 0.700–0.993, P = 0.041) increased the risk of therapeutic failure for MDR-E. coli infection. Conclusion The proportion of MDRO-PDAP has remained high in recent years. MDRO infection is more likely to result in worse outcomes. Dialysis age and previous multiple peritonitis infections were significantly associated with treatment failure. Treatment should be promptly individualized based on local empirical antibiotic and drug sensitivity analyses.